Research on the Mechanical Behavior and Rockburst Risk of the Deep-Buried Roadway at the Stratigraphical Boundary of Different Lithologies - Chaoqun Chu; Lei Xia; Shunchuan Wu; Shun Han; Guang Zhang (Applied Sciences, 2025)
It has been found in engineering practice that the degree of rockburst risk increases when roadway excavation occurs near the stratigraphical boundary of different lithologies. This study uses the 1276 m deep-buried roadway of a lead–zinc mine in Yunnan, China, as its engineering background. Based on a numerical analysis of this case, it investigates the mechanical behavior of surrounding rocks in different lithological formations and explores the causes of excavation-induced rockburst. Additionally, by changing the excavation strategy in a numerical simulation, the influence of the direction of roadway excavation on the degree of rockburst risk in the construction of different lithological formations is assessed. The results are summarized as follows: (1) When the tunnel passes from the C1b stratum (limestone) to the D3zg stratum (dolomite), an abnormal stress zone forms in the roof rock strata of the D3zg stratum (the lower plate of the stratum boundary). The rockburst risk level was evaluated by introducing the numerical rockburst index in this abnormal stress zone, which aligns closely with on-site rockburst investigation results. The rockburst risk is the greatest in the abnormal stress zone, which provides an external energy storage environment for the development of rockburst disasters. (2) Near the stratum boundary, the rockburst risk level when excavating from the D3zg stratum to the C1b stratum is greater than that when excavating from the C1b stratum to the D3zg stratum. The direction of tunnel excavation significantly affects the rockburst risk level during construction that crosses different lithological strata. These findings can provide a theoretical basis for the construction design of similar underground projects.